# 1 multiply with distributive property: problems 1 standard 10 multiply with distributive property:...

Post on 23-Dec-2015

216 views

Category:

## Documents

Embed Size (px)

TRANSCRIPT

• Slide 1
• 1 MULTIPLY WITH DISTRIBUTIVE PROPERTY: Problems 1 STANDARD 10 MULTIPLY WITH DISTRIBUTIVE PROPERTY: Problems 2 POLYNOMIALS MULTIPLY WITH DISTRIBUTIVE PROPERTY: Problems 3 USE DISTRIBUTIVE PROPERTY TO MULTIPLY BINOMIALS: Problems MULTIPLY BINOMIALS WITH F.O.I.L.: Problems and MODELING MULTIPLY POLYNOMIALS VERTICAL FORMAT: Problems DIFFERENCE OF SQUARES: Problems and MODELING PERFECT SQUARE TRINOMIALS: Problems and MODELING FACTORING GENERAL TRINOMIALS MODELING THIRD DEGREE POLYNOMIALS END SHOW PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 2
• 2 STANDARD 10: Students add, subtract, multiply, and divide monomials and polynomials. Students solve multi-step problems, including word problems, by using these techniques. ESTNDAR 10: Los estudiantes suman restan, multiplican, y dividen monomios y polinomios. Los estudiantes resuelven problemas de mltiples pasos, incluyendo problemas escritos, usando estas tcnicas. PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 3
• 3 It is possible to use the distributive property of multiplication over addition to multiply polynomials: STANDARD 10 Simplify 5y(6y + 5) =5y(6y) + 5y(5) 5y(6y + 5) =30y + 25y 2 MULTIPLYING POLYNOMIALS Simplify 6p(7p + 5) =6p(7p) + 6p(5) 6p(7p + 5) =42p + 30p 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 4
• 4 It is possible to use the distributive property of multiplication over addition to multiply polynomials: STANDARD 10 Simplify -8x(2x + 3x 6) 2 -8x(2x + 3x 6) 2 = -8x(2x ) + (-8x)(3x) + (-8x)(-6) 2 = -16x - 24x + 48x 3 2 MULTIPLYING POLYNOMIALS = (-8)(2)x + (-8)(3)x + (-8)(-6)x 2+1 1+1 Simplify -5x(3x + 2x 3) 2 -5x(3x + 2x 3) 2 = -5x(3x ) + (-5x)(2x) + (-5x)(-3) 2 = -15x - 10x + 15x 3 2 = (-5)(3)x + (-5)(2)x + (-5)(-3)x 2+1 1+1 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 5
• 5 It is possible to use the distributive property of multiplication over addition to multiply polynomials: Simplify 4x(2x y + 3x y 6x y ) 5 43 3 2 = (4x)(2x y) + (4x)(3x y ) + (4x)(-6x y ) 5 4 2 3 3 4x(2x y + 3x y 6x y ) 5 43 3 2 = (4)(2)x y + (4)(3)x y + (4)(-6)x y 1+5 1+4 1+3 2 3 =8x y + 12x y -24x y 6 5 2 4 3 STANDARD 10 MULTIPLYING POLYNOMIALS Simplify 3x(4x y + 5x y 7x y ) 6 43 3 2 = (3x)(4x y) + (3x)(5x y ) + (3x)(-7x y ) 6 4 2 3 3 3x(4x y + 5x y 7x y ) 6 43 3 2 = (3)(4)x y + (3)(5)x y + (3)(-7)x y 1+6 1+4 1+3 2 3 =12x y + 15x y -21x y 7 5 2 4 3 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 6
• 6 = (2x +1)(x + 4) (4)x (1) 2x x +2x +1(4) + = 2x + 9x + 4 2 = 2x + 8x + x + 4 2 = = (6x +3)(2x + 5) (5) (2x) (3) 6x (2x) +6x +3 (5) + =12x + 36x + 15 2 =12x + 30x + 6x + 15 2 = (6x - 3)(x + 5) (5) x (-3) 6x x +6x +(-3)(5) + = 6x + 27x - 15 2 = 6x + 30x -3x - 15 2 = (4x - 3)(3x - 7) (-7) (3x) (-3) 4x (3x) +4x +(-3) (-7) + =12x - 37x + 21 2 =12x -28x - 9x + 21 2 = Multiply the following binomials USING THE DISTRIBUTIVE PROPERTY: STANDARD 10 MULTIPLYING POLYNOMIALS = 2x(x+4) + 1(x+4) = 6x(2x+5) + 3(2x+5) (2x +1)(x + 4) (6x +3)(2x + 5) = (6x - 3)(x + 5) = 6x(x+5) + (-3)(x+5) = (4x - 3)(3x - 7) = 4x(3x-7) + (-3)(3x-7) PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 7
• 7 Simplify the following expressions: (6x +3)(2x + 5) (5) (2x) (3) 6x (2x) +6x +3 (5) + F O I L =12x + 36x + 15 2 =12x + 30x + 6x + 15 2 = (6x - 3)(x + 5) (5) x (-3) 6x x +6x +(-3)(5) + F O I L = 6x + 27x - 15 2 = 6x + 30x -3x - 15 2 = (4x - 3)(3x - 7) (-7) (3x) (-3) 4x (3x) +4x +(-3) (-7) + F O I L =12x - 37x + 21 2 =12x -28x - 9x + 21 2 = First Outer Inner Last: FOIL Method. STANDARD 10 MULTIPLYING POLYNOMIALS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 8
• 8 (2x +1)(x + 4) (4) x (1) 2x x +2x +1 (4) + F O I L = 2x + 9x + 4 2 = 2x + 8x + x + 4 2 = First Outer Inner Last: FOIL Method. STANDARD 10 MULTIPLYING POLYNOMIALS x x x 1 1 1 1 1 x + 4 2x + 1 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 9
• 9 Simplify the following expressions: (2x - 2)(3x - 1) (-1) (3x) (-2) 2x (3x) +2x+(-2) (-1) + F O I L = 6x - 8x + 2 2 = 6x -2x - 6x + 2 2 = First Outer Inner Last: FOIL Method. STANDARD 10 MULTIPLYING POLYNOMIALS x x x 3x 1 2x 2 x x PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 10
• 10 (2x 2)(x + 3) (3) x (-2) 2x x +2x +(-2) (3) + F O I L = 2x + 4x 6 2 = 2x + 6x -2x 6 2 = First Outer Inner Last: FOIL Method. STANDARD 10 MULTIPLYING POLYNOMIALS x x x 1 1 1 x + 3 2x 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 11
• 11 (2x 2)(x + 3) (3) x (-2) 2x x +2x +(-2) (3) + F O I L = 2x + 4x 6 2 = 2x + 6x -2x 6 2 = First Outer Inner Last: FOIL Method. STANDARD 10 MULTIPLYING POLYNOMIALS x x x 1 1 1 x + 3 2x 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 12
• 12 (2x 2)(x + 3) (3) x (-2) 2x x +2x +(-2) (3) + F O I L = 2x + 4x 6 2 = 2x + 6x -2x 6 2 = First Outer Inner Last: FOIL Method. STANDARD 10 MULTIPLYING POLYNOMIALS x x x 1 1 1 x + 3 2x 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 13
• 13 x+1x+1 X +5-3x +5x -3x 2 x 2 x 3 +5 +2x x 3 -2x 2 x- 4x + 7 2 x-4x-4 X -28+16x +7x -4x 2 2 x 3 -28 + 23x x 3 -8x 2 x- 3x + 5 2 2 x+1 x -4x + 7 2 x-4 STANDARD 10 MULTIPLYING POLYNOMIALS MULTIPLY VERTICALY: PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 14
• 14 x-2x-2 X - 8+4x -2x 2 2 x 3 - 8 +8x x 3 -4x 2 x - 3x + 6 2 x+3x+3 X +18- 9x +6x -3x 2 3x 2 x 3 +18 - 3x x 3 +0x 2 x -2x + 4 2 2 x-2 x -3x + 6 2 x+3 STANDARD 10 MULTIPLYING POLYNOMIALS MULTIPLY VERTICALY: +18 - 3x x 3 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 15
• 15 Difference of Two Squares: (x+2)(x-2) STANDARD 10 SPECIAL PRODUCTS x x 1 1 x +2 x 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 16
• 16 Difference of Two Squares: (x+2)(x-2) STANDARD 10 SPECIAL PRODUCTS x x 1 1 x +2 x 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 17
• 17 Difference of Two Squares: (x+2)(x-2) = x - 4 2 STANDARD 10 SPECIAL PRODUCTS x x 1 1 x +2 x 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 18
• 18 STANDARD 10 x x 1 1 1 x + 3 x 3 (x+3)(x-3) SPECIAL PRODUCTS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 19
• 19 STANDARD 10 x x 1 1 1 x + 3 x 3 (x+3)(x-3) SPECIAL PRODUCTS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 20
• 20 STANDARD 10 x x 1 1 1 x + 3 x 3 (x+3)(x-3) SPECIAL PRODUCTS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 21
• 21 STANDARD 10 x x 1 1 1 x + 3 x 3 (x+3)(x-3) = x 9 2 SPECIAL PRODUCTS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 22
• 22 Difference of Two Squares: (x+2)(x-2) = x - 4 2 (a+b)(a-b) = a - b 2 2 (3y+8)(3y-8) STANDARD 10 9y - 64 2 = (p+4)(p-4) = p - 16 2 (2y+5)(2y-5) 4y - 25 2 = SPECIAL PRODUCTS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 23
• 23 STANDARD 10 SPECIAL PRODUCTS (x +2) 2 = (x) + 2(x)(2) + (2) 2 2 x + 4x + 4 2 = x x 1 1 1 x +2 1 = (x+2)(x+2) PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 24
• 24 STANDARD 10 SPECIAL PRODUCTS (x +3) 2 = (x) + 2(x)(3) + (3) 2 2 x + 6x + 9 2 = x x 1 1 1 x +3 1 = (x+3)(x+3) 1 1 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 25
• 25 STANDARD 10 Perfect Square Trinomials: (a b) = a - 2ab + b 2 2 2 (a + b) = a + 2ab + b 2 2 2 (x +2) 2 (x +3) 2 = (x) + 2(x)(2) + (2) 2 2 = (x) + 2(x)(3) + (3) 2 2 = (5x) + 2(5x)(4) + (4) 2 2 (5x + 4) 2 (x - 5) 2 (x -7) 2 = (x) - 2(x)(5) + (5) 2 2 = (x) - 2(x)(7) + (7) 2 2 = (8x) - 2(8x)(4) + (4) 2 2 (8x - 4) 2 x + 4x + 4 2 = x - 14x +49 2 = 25x + 40x + 16 2 = x -10x + 25 2 = x + 6x + 9 2 = 64x - 64x + 16 2 = SPECIAL PRODUCTS PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 26
• 26 STANDARD 10 Multiply: (x+3)(x+2)(x+1) (x+2) (x+1) (x+3) (x + 2)(x + 3) (3) x (2) x x + x + (2) (3) + F O I L = x + 5x + 6 2 = x + 3x +2x + 6 2 = x+1x+1 X +6+5x +6x +5x 2 x 2 x 3 +6 +11x x 3 +6x 2 x +5x + 6 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 27
• 27 STANDARD 10 Multiply: (x+3)(x+2)(x+1) = x + 6x + 11x + 6 3 2 (x + 2)(x + 3) (3) x (2) x x + x + (2) (3) + F O I L = x + 5x + 6 2 = x + 3x +2x + 6 2 = x+1x+1 X +6+5x +6x +5x 2 x 2 x 3 +6 +11x x 3 +6x 2 x +5x + 6 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 28
• 28 STANDARD 10 Multiply: (x+3)(x+2)(x+1) = x + 6x + 11x + 6 3 2 (x + 2)(x + 3) (3) x (2) x x + x + (2) (3) + F O I L = x + 5x + 6 2 = x + 3x +2x + 6 2 = x+1x+1 X +6+5x +6x +5x 2 x 2 x 3 +6 +11x x 3 +6x 2 x +5x + 6 2 (x+2) (x+1) (x+3) So, a third degree polynomial may be represented GEOMETRICALLY, by the VOLUME OF A RECTANGULAR PRISM, in this case with SIDES (x+3), (x+2) and (x+1). PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 29
• 29 STANDARD 10 Multiply: (2x+1)(x+3)(x+4) (x+3) (x+4) (2x+1) (2x + 1)(x + 3) (3) x (1) 2x x +2x + (1) (3) + F O I L = 2x + 7x + 3 2 = 2x + 6x +1x + 3 2 = x+4x+4 X +12+28x + 3x +7x 2 8x 2 2x 3 +12 +31x 2x 3 +15x 2 2x +7x + 3 2 PRESENTATION CREATED BY SIMON PEREZ. All rights reserved
• Slide 30
• 30 STANDARD 10 Multiply: (2x+1